2022
DOI: 10.1186/s12882-021-02641-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, correlates and in-hospital outcomes of kidney dysfunction in hospitalized patients with heart failure in Buea-Cameroon

Abstract: Background Kidney dysfunction is common in patients with heart failure (HF) and has been associated with poor outcomes. This study aimed to determine the prevalence, correlates, and prognosis of kidney dysfunction in patients with HF in Cameroon, an understudied population. Methods We conducted a cross-sectional study in consecutive patients hospitalized with HF between June 2016 and November 2017 in the Buea Regional Hospital, Cameroon. Kidney dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In a cross-sectional study in which 74 patients with CHF were admitted consecutively, Jingi et al ( 29 ) showed that hypertensive disease (OR: 3.1, 95% CI: 1.2–8.4) was an independent risk factor for the development of renal insufficiency. This is consistent with our findings and suggests that comorbid hypertensive disease leads to a 2–3-fold increase in the risk of renal insufficiency in patients with CHF.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study in which 74 patients with CHF were admitted consecutively, Jingi et al ( 29 ) showed that hypertensive disease (OR: 3.1, 95% CI: 1.2–8.4) was an independent risk factor for the development of renal insufficiency. This is consistent with our findings and suggests that comorbid hypertensive disease leads to a 2–3-fold increase in the risk of renal insufficiency in patients with CHF.…”
Section: Discussionmentioning
confidence: 99%
“…Aims to determine the clinical correlates for the cardiorenal anemia syndrome at baseline among the patients with heart failure irrespective of ejection fraction [ 2 , 6 , 24 , 25 ]. Information from medical records such as chronic kidney disease using serum creatinine level and echocardiographic report will be accessed from 18 th February, 2023 onwards.…”
Section: Methodsmentioning
confidence: 99%
“…Renal dysfunction, indicated by elevated blood creatinine or decreased eGFR, is commonly associated with disease progression and poor clinical outcomes [ 40 , 41 ]. In chronic conditions, such as HF, diabetes, and hypertension, a continuous decline in eGFR indicates progressive loss of renal units, potentially related to intraglomerular hypertension or chronic hypoperfusion damage [ 42 ].…”
Section: Subgroups Of Patients With Hf and Gdmt Explorationmentioning
confidence: 99%